Network Meta-Analysis of 10 Storage Mediums for Preserving Avulsed Teeth - Zhang, Na; Cheng, Yuzhao; Li, Fenglan; Kang, Qian (Frontiers in Medicine, 2021)
Many storage medium are available to store avulsed tooth for preserving the viability of periodontal ligament (PDL) cells before replantation, however it’s unclear which media may be the optimal option. We performed this network meta-analysis to answer this question. A comprehensive search was conducted in PubMed, EMBASE, and the Cochrane library to capture eligible studies investigating the comparative efficacy of Hank's balanced salt solution (HBSS), aloe vera gel (AVG), oral rehydration solution (ORS), coconut water, egg white, green tea, propolis, saline, milk, and water. Statistical analysis was conducted using Review Manager v5.3 and ADDIS v1.16.8. Twenty RCTs involving 31 reports were included finally. Direct meta-analysis suggested that HBSS was superior to ORS, milk, saline, and water, ORS was superior to milk but inferior to coconut water and propolis, egg white was superior to milk but inferior to AVG and propolis, propolis was superior to AVG, milk, and saline, and coconut water and water was inferior to saline and milk respectively. Network meta-analysis suggested that AVG was inferior to other nine medium, and propolis was superior to HBSS (SMD, -5260.24; 95% CrI, -10447.39 to -70.37) and milk (SMD, -5461.11; 95% CrI, -10574.99 to -328.51). Moreover, ranking probabilities indicated the highest probability for propolis, followed by saline, ORS, HBSS, milk, egg white, water, green tea, and AVG successively. Propolis may be the optimal media for storing avulsed tooth before replantation. However, given the availability of propolis and HBSS and the hypotonic properties of saline, ORS or milk should also be preferentially selected.